Homogeneous platinum diselenide metal/semiconductor coplanar structure fabricated by selective thickness control. Issue 44 (5th November 2019) - Yang, Yajie; Jang, Sung Kyu; Choi, Haeju; Xu, Jiao; Lee, Sungjoo
Abstract : Exploiting the layer-dependent semiconductor-to-semimetal transition property, a PtSe2 device with homogeneous coplanar structure demonstrate high mobility and extremely low contact resistance. Abstract : For the realization of two-dimensional material-based high-performance electronic devices, the formation of a stable, high-quality metal–semiconductor contact is a key factor. Platinum diselenide (PtSe2 ), a group-10 transition metal dichalcogenide, is a promising candidate owing to its unique property of layer-dependent semiconductor-to-semimetal transition. Here, a scalable and controllable method utilizing an inductively coupled plasma treatment is reported for selectively controlling the thickness of PtSe2 flakes. The PtSe2 transforms from a semimetal to a semiconductor when the thickness decreases below 3 nm. A field-effect transistor is fabricated based on the homogeneous platinum diselenide metal/semiconductor coplanar structure (metallic PtSe2 as source/drain electrodes and semiconductor PtSe2 as a channel), which demonstrates a low contact resistance of 362 Ω μm and carrier mobility of 150 cm 2 V −1 s −1, outperforming the previously reported PtSe2 -based devices.